1996
DOI: 10.3382/ps.0750962
|View full text |Cite
|
Sign up to set email alerts
|

Duration of Fertility in Ad Libitum and Feed-Restricted Caged Broiler Breeders

Abstract: It has been shown in previous studies that fertility can be reduced in overweight broiler breeder (BB) flocks. In an effort to determine the effect of ad libitum feeding on the duration of fertility in BB hens, 60 52-wk-old Shaver Starbro hens were randomly assigned to one of two treatments, ad libitum feeding (F) or restricted feeding (R) to maintain breeder target weights. All hens were reared to 52 wk under conditions of feed restriction. All birds were weighed individually on a weekly basis. At the beginni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
3

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 5 publications
0
16
3
Order By: Relevance
“…This finding differs from that for broiler breeders (Goerzen et al, 1996); the reason may be that hens were at different ages and had different amounts of fat deposit which greatly influences body weight, laying rate and reproduction performance (Bilgili and Renden, 1985). In an earlier study, Beaumont et al (1992) reported a positive relationship between laying rates and duration of fertility in laying hens, whereas we found a negative relationship between these variables.…”
Section: Decontrasting
confidence: 84%
See 2 more Smart Citations
“…This finding differs from that for broiler breeders (Goerzen et al, 1996); the reason may be that hens were at different ages and had different amounts of fat deposit which greatly influences body weight, laying rate and reproduction performance (Bilgili and Renden, 1985). In an earlier study, Beaumont et al (1992) reported a positive relationship between laying rates and duration of fertility in laying hens, whereas we found a negative relationship between these variables.…”
Section: Decontrasting
confidence: 84%
“…Although duration of fertility may be predicted from data obtained from egg collection intervals of 18 to 21 d (Kirby and Froman, 1990), such an interval may seem impractical, especially if overall fertility is the only variable of interest. Previous work has indicated that DF varies with laying intensity (Beaumont et al, 1992;Goerzen et al, 1996). The aim of this study was to determine which one of the three means of describing fertility is best for assessing the ability of storing sperm in hens and whether fertility and laying intensity should be combined with this assessment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rosebrough et al (1983) found that energy and protein utilisation for egg production in large white turkeys was better in birds fed lower protein and energy diets and Scott et al (1999) found that feeding laying hens diets containing protein levels between 16 and 19% had no significant effect on egg production. Similarly, Goerzen et al (1996) reported no difference in egg production between hens fed ad libitum and those on a restricted diet. Malden et al (1979) indicated that if broiler breeders were allowed to get too fat, egg production would be depressed during the laying period possibly because, as suggested by Badley (1997), excess fat deposits can prevent eggs from being deposited in the oviduct.…”
Section: Introductionmentioning
confidence: 95%
“…The continuous genetic improvement of broilers, particularly for rapid growth, better feed efficiency, and higher meat yield implies in constant changes in bird management and feeding. In broiler breeders, in particular, this means preventing the negative effects of excessive body weight on reproductive performance (Goerzen et al, 1996;Barbato, 1999;Romero-Sanchez et al, 2007).…”
Section: Introductionmentioning
confidence: 99%